PENINGKATAN KOMPETENSI MENGAPRESIASI SASTRA MELALUI SIARAN PEMBINAAN BAHASA INDONESIA DI RADIO REPUBLIK INDONESIA SURAKARTA - Rahmawati, Laili Etika; Al-Ma’ruf, Ali Imron; Pratiwi, Dini Restiyanti (Universitas Muhammadiyah Surakarta, 2016)
The aim of the society services through the air broadcast in Radio of Indonesian Republic of Surakarta were: (1) to improve the societyâs motivation, especially for them who were students in order to appreciate the literature; (2) to improve the societyâs concerns, especially for those who students in improving their literature appreciation ability in order to attain the man who has wise character because the literature have the education values which could be the basic consideration in conducting the behaviour; (3) to enlarge the listenersâÂ knowledge, especilly for the students who need the knowledge of linguistics, literature, and its teaching; (4) to create the institution cooperation between the Muhammadiyah University of Surakarta and the government institution i.e. Radio of Indonesian Republic o f Surakarta. The social service was conducted in RRI Surakarta, in the form of speech broadcast, based on the paper prepared before. The broadcast activity is conducted by recording before its on air. The recording process used the facility of RRI Surakarta by the guidance of RRI Surakarta staff as the responsible or the recording section. The broadcast is delivered by a speaker with the different topics but in the same theme. The broadcast theme of the three months is âImproving the Ability of Literature Appreciation through the Broadcast Guidance of Bahasa Indonsia in RRI Surakartaâ. The six times broadcast activity planned for three months can be conducted four times of new broadcast and twice of recorded broadcast.